IMPLEMENTASI POAC MANAJEMEN MUTU PENDIDIKAN BERBASIS NILAI-NILAI PROFETIK DALAM MEWUJUDKAN MUTU GURU : STUDI MULTI - SITUS DI MAN SE-KABUPATEN LOMBOK TENGAH - Lalu Misban; Muhanmmad; Edi Muhammad Jayadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses the implementation of POAC (Planning, Organizing, Actuating, and Controlling) in educational quality management based on prophetic values to enhance teacher quality in a multi-site study across state Islamic senior high schools (MAN) in Central Lombok Regency. This study employed a qualitative approach with a multi-site study design conducted in several madrasahs within the MAN cluster in Central Lombok Regency. Data were collected through in-depth interviews, observations, documentation studies, and focus group discussions, and were then analyzed thematically using triangulation technique.The findings reveal that the planning function is reflected in the formulation of work programs and teacher development planning that emphasize honesty, responsibility, and a vision for quality. The organizing function is evident in task distribution, team coordination, and the management of resources in a trustworthy manner. The actuating function is manifested through the communicative leadership of madrasah principals who motivate and provide prophetic role models. Meanwhile, the controlling function is carried out through supervision, periodic evaluation, and follow-up actions for quality improvement. The integration of prophetic values such as ṣidq (truthfulness), amanah (trustworthiness), tabligh (communicativeness), and fathanah (wisdom/intelligence) strengthens teacher professionalism, improves discipline, and fosters a quality-oriented work culture. Therefore, POAC based on prophetic values is considered a relevant approach to strengthening teacher quality within the madrasah contextKeywords: Management, Character Development, Tahfiz Program